ANALYZING THE IMPACT OF PRODUCT QUALITY, PRICE PERCEPTION, BRAND IMAGE, AND SERVICE QUALITY ON CONSUMER SATISFACTION IN ONLINE PURCHASING (A CASE STUDY OF SUMBER MAS GOLD STORE, SEMARANG) - Al Falah, Adib Muhammad; Maskur, Ali (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of product quality, price perception, brand image, and service quality on consumer satisfaction in online purchases at Toko Emas Sumber Mas in Semarang. Using a quantitative approach, data were collected through questionnaires from 99 respondents and analyzed using multiple linear regression with SPSS software. The results show that simultaneously, the four independent variables significantly affect consumer satisfaction. Partially, price perception, brand image, and service quality have a positive and significant influence, while product quality does not have a significant effect. These findings indicate that in online transactions, value-oriented aspects such as fair pricing, brand reputation, and responsive service play a more critical role in determining consumer satisfaction than product quality alone. The practical implication suggests that businesses should focus on strengthening price perception, enhancing brand image, and optimizing service quality to improve consumer satisfaction and loyalty